Sie sind auf Seite 1von 13

Background Trigonometry is about measurement with triangles.

We will start by
reviewing/discussing some basics of triangles. We will also discuss some basics from
algebra such as the distance between two points, and parallel and perpendicular lines.
A Triangle An angle is two rays with a common endpoint (known as the vertex of
the angle). The rays are known as the sides of the angle.

A triangle is three (3) noncollinear points (known as the vertices) and the connecting
line segments (known as the sides).

We name the sides using the vertices, A, B, C:

side AB
side AC
side BC

A Basic Facts for triangles are The sum of the measures of the angles is 180o.
Geometry While discussing basic facts, we have the following important facts from
1. Vertical angles have equal measures.

When two lines intersect, such as line AB and line RS shown at the left, angle AOS
and angle ROB are known as vertical angles- as are angle AOR and angle SOB. If
angle AOS has measure 40o then angle ROB has measure 40o.

2. For parallel lines ( non-intersecting lines) cut by a transversal, alternate interior

angles have equal.
Angle ABC and angle CDE are known as alternate interior angles. Also, angle FBC
and angle GDC are alternate interior angles.

In the above drawing, if the measure of angle ABC is 40o then the measure of angle
CDE is also 40o. Also, because angle ABC and angle FBC are supplementary
angles (their measures sum to 180o) we know that the measure of angle FBC is 140o.
What is the measure of angle CDG? Answer 140o.

Right Triangle A right triangle is a triangle containing a right angle (an angle with
measure 90o). The largest side in a right triangle is the side opposite the right angle
(why?). This longest side is known as the hypotenuse. The other two sides are known
as the legs. We have following property (known as the Pythagorean Theorem):
For any right triangle (see drawing) we have that the longest side, the hypotenuse,
squared equals the square of one leg plus the square of the other leg.
c2 = a2 + b2

Cosine angle A is the ratio of x to r

Tangent angle A is the ratio of y to x
Pythagorean Identity Another identity that is very useful is the Pythagorean
sin2 A + cos2 A = 1
A proof of this identify is as follows:

From the definition of sine and cosine, we have:1 = cos2 A + sin2 A

Example 6 If cos B = -3/4 and the terminal side of angle B is in quadrant III then
sin B = ______

and tan B = ______

Applications Basically, trigonometry was developed as a way of indirectly

measuring a distance or an angle (such as finding the distance to the moon or to a
star). We will start with a simple surveying problem.

Example 6 From the top of a 300 foot cliff a boat is spotted at an angle of
depression of 23o and sailing directly toward the cliff. One minute
later, the boat is spotted at an angle of depression of 30o.
How far has the boat traveled in the 1 minute?

The distance, d, is d = x - y
So, we need to find x (the original distance) then y (the distance an 1 minutes later)
and then find the difference, d.

Radian Measure The radian measure of an angle is the ratio of arc length to
radius. Thus, for the 40o angle in Example 3 we have a radian measure of (10/9) : 5
or 2/9. Note that the radian measure (like the degree measure) is independent of the
size of the circle. If the circle in Example 3 had radius 1, then the arc length would
have been (40/360)(2) or 2/9 and the radian measure would be (2/9) : 1 or 2/9.
Unit Circle When converting from a degree measure to a radian measure it is
helpful to use a circle of radius 1, a unit circle. The equation for this circle is x2 + y2
= 1. Consider a 60o angle and the unit circle:
The circumference of the unit circle is 2. So, the radian measure is (60/360)(2) or
/3. Some important correspondences between degree measures and radian measures
are (know these):
Degree 0
Radian 0
/6 /4

3/2 2

Working with Trigonometry Expressions Just as we have standard polynomials

(no parentheses, no like terms, and written in decreasing order of the terms) as well as
completely reduced rational expressions (numerator and denominator have no
common factors); we have completely reduced trigonometric expressions. Work
through the following examples.
Example 1 Write as a completely reduced trigonometric expression:
(sin x + 1)(sin x - 1)
Solution We begin by removing the parentheses.
(sin x + 1)(sin x - 1) = sin2 x + sin x - sin x - 1
= sin2 x - 1

Example 2 Write as a completely reduced trigonometric expression:

(cos x + 1)2
Solution We begin by removing the parentheses.
(cos x + 1)(cos x + 1) = cos2 x + cos x + cos x + 1
= cos2 x + 2cos x + 1
Factoring Just we can do operations like addition and multiplication on
trigonometric expressions, we can also factor (write as a product) trigonometric
polynomials. Work through the following example.
Example 5 Completely factor sin2 x - 3sin x
Solution As with any factoring, we look for a common factor, sin x in this case.
sin2 x - 3sin x = (sin x)(sin x - 3)
Example 6 Completely factor 2cos2 x - 9cos x - 5
Solution As with any factoring, we start by looking for a common factor, there is
none in this case. Now, just as 2x2 - 9x - 5 factors as (2x + 1)(x - 5), the
trigonmetric polynomial factors (using FOIL) as:
2cos2 x - 9cos x - 5 = (2cos x + 1)(cos x - 5)
Using the Identity sin2 x + cos2 x = 1 The wild card in trigonometry is its use of the
identity sin2 x + cos2 x = 1. Note that sin2 x + cos2 x = 1 yields the identities
sin2 x = 1 - cos2 x and cos2 x = 1 - sin2 x. Work through the following example.
Example 7 Completely factor 2cos2 x - 3sin x
Solution To factor (write as a product) we need to replace cos2 x with 1 - sin2 x:
2cos2 x - sin x = 2(1 - sin2 x) - 3sin x
= 2 - 2sin2 x - 3sin x
= -2sin2 x - 3sin x + 2
= -1(2sin2 x + 3sin x - 2)
= -1(2sin x - 1)(sin x + 2)
Trigonometric Fractions In addition to operations like adding, multiplying, and
factoring, we often will need to add and multiply fractions involving trigonometric
expressions. Work through the following example.
Example 8 Write as a completely reduced trigonometric expression containing only
the sine and cosine: 1 - tan2 A
Solution We start by replacing tan A with (sin A)/(cos A)

Example 11 Prove cos2 x - sin2 x = 2cos2 x - 1

Solution We start with the left member:

Although cos (A + B) is not equal to cos A + cos B, there is an identity for

cos (A + B).
Sum Identity: cos (A + B) = cos A cos B - sin A sin B
To prove this identity we use some basic geometry and algebra. We start with the unit

The distance from P to S equals the distance from Q to R because central angle POS
has the same measure as central angle QOR. Now, we use the distance between two
points formula from algebra.

Difference Identity Because cos (A - B) = cos (A + (-B)) we have:

cos (A - B) = cos(A + (-B))
= cos A cos (-B) - sin (A) sin (-B)
= cos A cos B + sin A sin B

[using the sum identity]

[using cos (-x) = cos x
and sin (-x) = -sin x]

Thus, the Difference Identity is: cos (A - B) = cos A cos B + sin A sin B
Example 5 Find cos 15o
Solution We use the fact that 15o is 45o - 30o. So, cos 15o = cos (45o - 30o).
Now, using the difference identity we have:

Sum Identity for Sine We now want to consider the sum and difference for the sine.
We start with a proof.

Of course we already know the above results as cos (90o - A) = sin A. That is, the
cosine of the complement of angle A is the sine of angle A. We can also write:
sin (90o - A) = cos A or

Using the above results we have

sin (A + B) = cos (/2 - (A + B))
= cos (/2 - A - B)
= cos ((/2 - A) - B)
= cos (/2 - A)cos B + sin(/2 - A)sin B
= sin A cos B + cos A sin B
So, Sum Identify for Sines is: sin (A + B) = sin A cos B + cos A sin B.
The Difference Identity for Sines Using sin A = -sin (-A) and cos A = cos (-A) we
Sin (A - B) = sin (A + (-B))
= sin A cos (-B) + cos A sin (-B)
= sin A cos B + cos A (-sin B)
= sin A cos B - cos A sin B
So, the Difference Identity for Sines is: sin (A - B) = cos A sin B - sin A cos B.
Below is a summary of the sum/difference identities. We will be more concerned with
working with these identities than memorizing them.
cos (A + B) = cos A cos B - sin A sin B
cos (A - B) = cos A cos B + sin A sin B
sin (A + B) = sin A cos B + cos A sin B
sin (A - B) = sin A cos B - cos A sin B
Sum and Difference Identities for the Tangent Using the ratio identity,
tan A = (sin A)/(cos A), and the sum and difference identities for Sine and Cosine, we

Using the identity tan (-A) = -tan A, we get the difference identity:

Double Angle Identities Using the fact that 2A is A + A, we have

cos (2A) = cos (A + A) = cos A cos A - sin A sin A = cos2 A - sin2 A
We can also write cos(2A) = cos2 A - (1 - cos2 A) = 2cos2 A - 1
And cos(2A) = (1 - sin2 A) - sin2 A = 1 - 2sin2 A
sin (2A) = sin (A + A) = sin A cos A + cos A sin A = 2sinA cos A
Example 9 If sin A = -2/3 with terminal side in Quadrant III and cos B = 1/3 with
terminal side in Quadrant I then find
a. sin ( A + B )

Phase Shift For g(x) = sin (x + /2) we say that we have a translation to the left of
/2 units. In trigonometry this is known as a phase shift of /2 units to the left.
Consider the following table of values:

The Sine Law The lengths of the sides are directly proportional to the sines of the
angles opposite the sides.
That is, the ratio of sides equals to ratio of the sines of the angles opposite the sides.

Cosine Law The square of one side of a triangle, say a, equals the sum of the
squares of the other two sides, say b and c, minus twice the product of
the other two sides and the cosine of the angle opposite side a.

We can establish the cosine law by drawing an altitude, h, to the base of a triangle.
Now from triangle BCD,
a2 = h2 + (c - x)2
a2 = h2 + c2 - 2cx + x2
a2 = h2 - 2cx + x2 + c2
We also have (from triangle ACD)
b2 = h2 + x2 or x2 = b2 - h2
So, a = h2 - 2cx + b2 - h2 + c2
a2 = b2 + c2 - 2cx

Using triangle ACD again we have cos = x/b or x = bcos .

Thus, we get a2 = b2 + c2 - 2cbcos

Example 5 Joel leaves camp on a heading of N 20o W and hikes 15 miles. He then
turns to a heading of S 42o E and hikes 8 miles. How far is Joel from